Freestyle Swimming Training Model Based on Traditional Games to Improve Swimming Achievement in Children Aged 10-15 Years - Rezki Rezki; Gusril Gusril; Arsil Arsil; Alnedra Alnedra; Bafirman HB; Anton Komaini Anton Komaini (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2025)
The purpose of the study. This study aims to develop a freestyle swimming training model based on traditional games, designed to improve athletes' performance in the 50-meter freestyle event. The main issue faced by athletes in Kampar Regency is the difficulty in achieving optimal performance times in freestyle swimming. Therefore, this training model was developed as an innovative solution to address these challenges, with the hope of significantly enhancing the quality of training and athletes' performance. Materials and methods. This research is a Research and Development (R&D) study focused on the development of a swimming training model with a holistic approach, using the Borg and Gall development model, which consists of 10 stages: (1) Research and information collecting, (2) Planning, (3) Development of preliminary form of product, (4) Expert validation, (5) Revision of expert validation results, (6) Main field testing, (7) Operational product revision, (8) Operational field testing, (9) Final product revision, and (10) Dissemination and implementation. The research design used for effectiveness testing is the pre-test post-test control group design. Results. The results of this study include 10 freestyle swimming training models based on traditional games using targets. The validation results indicate that this training model has a high validity level, with a strong score of 0.85 based on the Aiken scale. The practical assessment results show that this model is highly practical, with an average score of 86.46% based on the Guilford scale. The pre-test and post-test data from 8 athletes show a significant improvement in their 50-meter freestyle performance after the training model was applied. The effectiveness test results for the overall data show a t-value of (2.85) > t-table (2.36). Conclusions. Therefore, it can be concluded that the freestyle swimming training model based on traditional games with targets is more effective than the conventional training model in improving freestyle swimming performance.